4 - Économie solidaire et espace public en Afrique : le cas de la région de Marrakech: https://doi.org/10.4314/ad.v35i4.70217 - El Morchid, Brahim (Africa Development, 2021)
The interaction between the economy of solidarity and public space gives rise to growing interest, both due to the theoretical debates it implies and in light of the socioeconomic realities it involves. The present contribution does not aim to paint a complete picture of the debates on this theme. After explaining the crucial role of public space in any clear understanding of the economy of solidarity, we will focus on explaining the mechanisms whereby the activities pertaining to the economy of solidarity give new impetus to public space. Finally, through a monographic study, we will test the contributions made by the literature relating to this issue.